DAMPAK PANDEMI COVID-19 TERHADAP KINERJA KEUANGAN PADA PT. TELKOM TBK - Saodah, Aas; Afrianandra, Cut (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
The purpose of the study is to analyze the impact of the Covid-19 pandemic on the financial performance of PT. Telkom Tbk. The type of research used is quantitative research with a descriptive approach. In this study, we do not use a population but rather a social situation composed of three elements: place, actor, and activity. The subject of this research is PT. Telkom Tbk as triangulation. Secondary data is used in the form of PT. Telkom's financial statements for the 2019-2021 period. The techniques used in data collection include observation, interviews, and documentation. The data analysis approach is descriptive qualitative. Financial performance is measured by several ratios, namely liquidity ratios, solvency ratios, activity ratios, and profitability ratios. This study indicates that the covid-19 pandemic has both a negative and a positive impact on PT. Telkom Tbk's financial performance. Ratio calculation data demonstrate that the company has decreased in some of the ratios analyzed. This decrease does not have a detrimental effect on the financial performance of PT. Telkom Tbk, as it can be offset by increases in several other ratios.